2015
DOI: 10.12968/jowc.2015.24.10.478
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pressure ulcers in patients with declining renal function using arginine, glutamine and ß-hydroxy-ß-methylbutyrate

Abstract: The aim of this study is to examine the efficacy on healing pressure ulcers (PU) of using a supplement combination containing arginine, glutamine and ß-hydroxy-ß-methylbutyrate, which was given to two elderly patients with renal dysfunction. The PU was surgically opened, decompressed and treated by drugs. A half quantity of the defined dose of the supplement combination, with an enteral nutrition product, was administered to the patients twice a day. This combination improved the PUs, with no effect on renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Collectively, evidence suggests that giving patients high energy, high protein ONS enriched with arginine, zinc, and antioxidants is helpful in reducing PI occurrence, PI size, and improving healing. 6,7,[11][12][13][14][15][16][17] Studies show that effective strategies that optimize oral nutritional care are those that are evidence based, timely, standardized, scheduled, and consistent with maximization of the EHR and CDSSs. 31,32,38,39,47…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, evidence suggests that giving patients high energy, high protein ONS enriched with arginine, zinc, and antioxidants is helpful in reducing PI occurrence, PI size, and improving healing. 6,7,[11][12][13][14][15][16][17] Studies show that effective strategies that optimize oral nutritional care are those that are evidence based, timely, standardized, scheduled, and consistent with maximization of the EHR and CDSSs. 31,32,38,39,47…”
Section: Discussionmentioning
confidence: 99%
“…2,3,9,10 Recent studies have reported valuable strategies that have been shown to improve nutrition for the prevention of PI in hospitalized patients. [5][6][7][11][12][13][14][15][16][17][18][19] Knowledge of these strategies, as well as identification of potential barriers in implementation, will empower clinicians to optimize their resources and provide the best care for hospitalized patients. 20…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The combination of Gln/Arg/HMB may improve recovery through various mechanisms in patients undergoing heart surgery. This compound had beneficial effects on vascular endothelial function [ 31 ], intestinal injuries [ 32 ], pressure ulcers [ 20 , 33 ], immune function [ 34 ], and anastomosis healing [ 35 ]. Moreover, it may prevent muscle wasting [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some specific nutrients that are involved in the wound healing process should be considered as pharmaconutrients, and those are mainly proteins, arginine, glutamine, zinc, β-hydroxy-β-methylbutyrate, and vitamin C (22). The effect of these nutrients depends on the local circulation in the wound region, which determines efficient nutrient transfer and local metabolism as well as the elimination of toxic cellular metabolites (23).…”
Section: Chronic Wounds and Pressure Ulcersmentioning
confidence: 99%